Oral health: Epidemiology and concordance in Australian children and parents - Stormon, Nicole; Clifford, Susan; Lange, Katherine; Mangoyana, Clare; Ford, Pauline; Wake, Melissa; Lalloo, Ratilal (My University, 2022)
Studying parent-child pair health provides the opportunity to identify risk factors and opportunities for oral health prevention and intervention focusing on the family context. The aim of this study was to describe the oral health of children aged 11-12 years and their parents in a national sample of parent-child dyads in Australia. The Child Health CheckPoint is a study of 11 to 12-year-old children and one parent nested within the Longitudinal Study of Australian Children, a nationally representative cohort study. In 2015-16, the study collected two-dimensional photographic intra-oral images and was scored using visual assessments of the teeth, oral hygiene and malocclusion. Of the 1874 CheckPoint families, 1396 biological parent-child pairs had at least one oral health measure recorded. Over two-thirds of children had moderate to severe gingival inflammation (69.7%, 95%CI 64.7-74.9). Parents had a lower proportion of poor oral hygiene (2.1%, 95% CI 1.4-3.0) than children (13.0%, 95% CI 11.3-14.9). High concordance was seen in the Modified Gingival Index correlation coefficient 0.49 (95%CI 0.44-0.53). The high concordance in gingival health between child-parent pairs supports the familial and behavioural links established in previous studies. Children had poorer oral hygiene but fewer visible dental caries lesions than their parents. As dental caries is a chronic and cumulative disease, preventive interventions targeting children's oral hygiene are needed.
Community Dentistry and Oral Epidemiology
Keywords: Childhood and child development; Families and relationships; Health and wellbeing